COSMIC RAY INTENSITY VARIATIONS DURING 1967. - Sandstrom,Arne E.; Dyring,Eric; Larfors,Ove; Lindgren,Stig; Sporre,Bert (1968)
The recording of cosmic ray intensity time variation was continued as during the last few years by means of one neutron monitor, one cubical telescope and four inclined telescopesin Uppsala and Kiruna. Tables and figures give a detailed account of diurnal and semidiurnal variations during 1967. Nine decreases are reproduced in one-hour diagrams. (Author)